1972
DOI: 10.1029/wr008i002p00410
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic model of runoff‐producing rainfall for summer type storms

Abstract: Modification of watersheds occurs either through natural processes, such as erosion, or human influences, such as urbanization. In either case the rainfall input must be properly modeled before the runoff output can be predicted as the modifications take place. The paper considers runoff‐producing summer precipitation of short duration and high spatial variability as an intermittent stochastic phenomenon. The probability distribution of seasonal total point or areal rainfall is obtained by convoluting a Poisso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

1977
1977
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 6 publications
0
12
0
3
Order By: Relevance
“…Gaiha et al (2010) used negative binomial regression to assess the likely count of natural disasters in various countries. Duckstein et al (1972) showed that the distribution for mean areal rainfall in arid climates could be described by a negative binomial probability mass function (pmf). Czamara et al (1997) used negative binomial (Pascal) distribution to analyse number of droughts in time interval (0, r) along with chisquare tests of goodness of fit at the 0.05 level.…”
Section: Methodsmentioning
confidence: 99%
“…Gaiha et al (2010) used negative binomial regression to assess the likely count of natural disasters in various countries. Duckstein et al (1972) showed that the distribution for mean areal rainfall in arid climates could be described by a negative binomial probability mass function (pmf). Czamara et al (1997) used negative binomial (Pascal) distribution to analyse number of droughts in time interval (0, r) along with chisquare tests of goodness of fit at the 0.05 level.…”
Section: Methodsmentioning
confidence: 99%
“…Outside hydrology there have as yet been only few applications of this socalled 'Box-Jenkins' approach to pure time series; notable exceptions are the work by Bennett et al (1976) modelling atmospheric pollution at Kew, an analysis of soil tension by Lai (1976) and of sediment yield by Duckstein et al (1976). Rather more work has been carried out using the same approach but analysing distance series in which time is replaced by distance along some natural transect such as down a river or downslope.…”
Section: Markov Processesmentioning
confidence: 98%
“…Exponential, gamma, Weibull and lognormal probability distributions have been applied. Duckstein et al (1972) fitted the exponential distribution. Mills (1981) modelled total amount with the lognormal distribution, observing the mean to be a function of duration and the variance to be independent.…”
Section: Modelling Rainfall Amounts On Wet Daysmentioning
confidence: 99%